(untitled) (Damascus University Journal of agriculture sciences, 2022)
This research was conducted in Tartous Governorate in 2019-2020 to evaluate the efficacy of grafting on (TANTAN) origin and bio-fumigation in controlling Meloidogyne incognita on peppers (Dallas variety) in greenhouses, and comparing it with two commonly used pesticides in the region Vydate (Oxamyl) and (Fluopyram) Velum prime. And study the effect of these treatments on plant productivity and nematode density in the soil and calculate the gall index. The results showed an increase in the average productivity of the plant compared to the control, where the grafting treatment was significantly superior to the resistant root (4.75 kg/plant), followed by the treatment of Oxamyl (4,58 kg/plant) over the other treatments, and a decrease in the average nematode density was also recorded in all Transactions compared to the control, and the bio-fumigation treatment was recorded (1.1 second larvae/100 cm3 soil), followed by the grafting treatment on a resistant origin (3.89 second larval stage/100 cm3 soil), and the lowest average root complex coefficient was recorded at least in the grafted plant (1.83) and bio-fumigation (2,03) for the rest of the transactions.